Influence of health locus of control and fear of hypoglycaemia on glycaemic control and treatment satisfaction in people with Type 1 diabetes on insulin pump therapy. Issue 5 (20th February 2017) - Indelicato, L.; Mariano, V.; Galasso, S.; Boscari, F.; Cipponeri, E.; Negri, C.; Frigo, A.; Avogaro, A.; Bonora, E.; Trombetta, M.; Bruttomesso, D.
Abstract: Aim: To assess the influence of health locus of control and fear of hypoglycaemia on metabolic control and treatment satisfaction in people with Type 1 diabetes mellitus on continuous subcutaneous insulin infusion. Methods: People with Type 1 diabetes on continuous subcutaneous insulin infusion for at least 1 year, sub‐classified as an 'acceptable glucose control' group [HbA1c ≤ 58 mmol/mol (7.5%)] and a 'suboptimum glucose control' group [HbA1c > 58 mmol/mol (7.5%)], were consecutively enrolled in a multicentre cross‐sectional study. Questionnaires were administered to assess health locus of control [Multidimensional Health Locus of Control (MHLC) scale, with internal and external subscales], fear of hypoglycaemia [Hypoglycaemia Fear Survey II (HFS‐II)] and treatment satisfaction [Diabetes Treatment Satisfaction Questionnaire (DTSQ)]. Results: We enrolled 214 participants (mean ±sd age 43.4 ± 12.1 years). The suboptimum glucose control group ( n = 127) had lower mean ±sd internal MHLC and DTSQ scores than the acceptable glucose control group (19.6 ± 5.2 vs 21.0 ± 5.0, P = 0.04 and 28.8 ± 4.8 vs 30.9 ± 4.5, P < 0.001). HFS‐II scores did not differ between the two groups. Internal MHLC score was negatively associated with HbA1c ( r = −0.15, P < 0.05) and positively associated with the number of mild and severe hypoglycaemic episodes ( r = 0.16, P < 0.05 and r = 0.18, P < 0.001, respectively) and with DTSQ score ( r = 0.17, P < 0.05). HFS‐II score was negatively associated with DTSQ score ( r = −0.18, P < 0.05) and positively with number of severe hypoglycaemic episodes ( r = 0.16, P < 0.5). Conclusions: In adults with Type 1 diabetes receiving continuous subcutaneous insulin infusion, high internal locus represents the most important locus of control pattern for achieving good metabolic control. What's new?: Locus of control (the combination of expectancies about sources of behaviour reinforcement) can be internal (success linked to patient efforts) or external (success linked to external factors). In people with Type 1 diabetes, the influence of locus of control and fear of hypoglycaemia on metabolic outcomes and treatment satisfaction is unclear. We found that internal locus of control is associated with greater glucose control and treatment satisfaction in people on pump therapy, while fear of hypoglycaemia is unrelated to glycaemic control and inversely related to treatment satisfaction. Analysing psychological variables may enable caregivers to improve patients' ability to handle diabetes.